The Effect of Education, Training, and Self-Efficacy on Interest in Entrepreneurship Through Motivation in BTN Santri Developer Kebangsaan Training Participants in Java - Nurullah, Tubagus Saef; Putra, Suadi Sapta; Yuliantini, Tine; Hotimah, Husnul (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This research aims to analyze the influence of education, training, self-efficacy on entrepreneurial interest with motivation as an intervening variable.  The total sample was 131 respondents National Savings Bank National Savings Bank Training Participants Alumni on the island of Java who were taken using a questionnaire. Data analysis was carried out with SEM Smart PLS 4.0.9.9. The results showed that the influence of education and self-efficacy on positive motivation was significant, the influence of training on positive motivation was not significant, the influence of training and motivation on entrepreneurial interest was significantly positive, the influence of education on entrepreneurial interest was negative and not significant. Self-efficacy towards negative entrepreneurial interest. The role of motivation mediates the influence of education and self-efficacy on entrepreneurial interest, whereas motivation does not mediate the influence of training on entrepreneurial interest.